Endothelial function can be modulated by acute hyperglycemia - Hassanain Qambari; Paula K. Yu; Chandrakumar Balaratnasingam; Jayden Dickson; Dao-Yi Yu (Scientific Reports)
Abstract Endothelial dysfunction is a known consequence of chronic hyperglycemia and a major pathogenic factor for microvascular diseases such as diabetic retinopathy. The effect and exposure period to acute hyperglycemia on the vascular endothelium, and its ability to recover from such exposure is less well understood. Here, we used an isolated perfused eye preparation to study the effect of acute hyperglycemia on the ocular microvascular endothelium of normoglycemic and 1-, 2-, 3-, and 4-week streptozotocin (STZ)-induced diabetic rats. The acetylcholine (Ach)-induced vasodilatory response was measured during sequential exposure to 6 mM (normoglycemic), 12 mM (mild hyperglycemic), 24 mM (hyperglycemic) and then again to 6 mM (normoglycemic) perfusates. Eyes were then processed histologically for examination of capillary density, capillary diameter, pericyte distribution, endothelial nitric oxide synthase (eNOS) distribution and accumulation of advanced glycated end products (AGEs). Ach responses were significantly enhanced in normoglycemic, 1-,2-, 3- and 4-week diabetic eyes after less than 2-h of high glucose (24 mM) exposure. Upon return to normoglycemia, Ach-induced responses in 1-, 2- and 3-week diabetic eyes were comparable with normoglycemic eyes. In the 4-week diabetic eyes, Ach-induced vasodilatory responses remained significantly enhanced despite restoration of normoglycemia. Capillary density and capillary diameter did not change significantly after 1-, 2-, 3- and 4-weeks of STZ-induced diabetes. Pericyte distribution significantly increased in all vascular layers of the 3- and 4-week diabetic eyes. eNOS immunoreactivity significantly increased in 1-week diabetic eyes. Significant AGEs immunolabelling was detected in the vascular basement membrane and intracellularly in 1-week STZ rats. These findings suggest that whilst endothelial function can recover after short term hyperglycemia, prolonged exposure (≥ 4 weeks) results in incomplete restoration, indicating a potential transition towards irreversible dysfunction.